2023
DOI: 10.1007/s13753-023-00468-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Thai Hospitals’ Evacuation Preparedness Using the Flexible Surge Capacity Concept and Its Collaborative Tool

Abstract: According to the concept of “flexible surge capacity,” hospitals may need to be evacuated on two occasions: (1) when they are exposed to danger, such as in war; and (2) when they are contaminated, such as during the Covid-19 pandemic. In the former, the entire hospital must be evacuated, while in the latter, the hospital becomes a pandemic center necessitating the transfer of its non-contaminated staff, patients, and routine activities to other facilities. Such occasions involve several degrees of evacuation—p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Increasing hospital beds [ 59 ] and discharging low-risk patients [ 58 ] have been identified as key components of surge capacity. However, surge planning includes four essential elements (4 S): [ 1 ] staff, including medical and non-medical personnel; [ 2 ] stuff such as medical devices and ambulances; [ 3 ] structures or spaces that need to be modified as treatment areas or shelters; and [ 4 ] systems that refer to practical or mutual guidelines [ 60 ]. Therefore, to increase hospital preparedness in surge capacity domain, it is necessary to plan and take necessary actions to increase the above-mentioned elements.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing hospital beds [ 59 ] and discharging low-risk patients [ 58 ] have been identified as key components of surge capacity. However, surge planning includes four essential elements (4 S): [ 1 ] staff, including medical and non-medical personnel; [ 2 ] stuff such as medical devices and ambulances; [ 3 ] structures or spaces that need to be modified as treatment areas or shelters; and [ 4 ] systems that refer to practical or mutual guidelines [ 60 ]. Therefore, to increase hospital preparedness in surge capacity domain, it is necessary to plan and take necessary actions to increase the above-mentioned elements.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, topics such as commitment, responsibility, and patient emotional support were extracted from the reviewed studies. Various studies have emphasized that preserving patients’ privacy and respecting their identity are essential moral values that become more important in emergencies such as disasters [ 5 , 45 ]. Hospital staff will face ethical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A disaster refers to any unexpected and sudden event that leads to the weakening and destruction of economic, social, and physical capabilities, resulting in life and financial losses, as well as the destruction of infrastructure facilities, economic resources, and employment opportunities within society [ 1 – 3 ]. While some disasters such as floods and hurricanes can be predicted to some extent, earthquakes remain less predictable [ 4 , 5 ]. Consequently, disaster preparedness becomes a fundamental principle in crisis management for any country, with a particular emphasis on safeguarding critical facilities like hospitals and their staff during such critical times [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the collaborative elements of Command and control, Safety, Communication, Assessment, Triage, Treatment, and Transport (CSCATTT), a recent review of Thai hospitals’ preparedness identified several shortcomings in each of these elements. Among the critical issues are insufficiencies in leadership, communication, mutual assessment abilities, triage, and transport [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential for hospital threats that might require evacuations such as flooding, fire or explosion, and the insufficient preparedness of the hospitals, partnerships and collaborations in DPHEs, [ 4 , 19 , 24 , 39 ], this study focused on developing collaboration using the FSC concept in response to hospital evacuation. To the best of our knowledge, this study is the first to assess collaboration and leadership among healthcare systems and external entities through simulation training which may offer an alternative way to explore and prepare hospitals for all aspects of surge capacity, including staff, stuff, space, and systems.…”
Section: Introductionmentioning
confidence: 99%